2020
DOI: 10.1016/j.adro.2019.09.002
|View full text |Cite
|
Sign up to set email alerts
|

Are Female Radiation Oncologists Still Underrepresented in the Published Literature? An Analysis of Authorship Trends During the Past Decade

Abstract: Purpose: We examined whether female authorship, traditionally underrepresented in the radiation oncology (RO) literature, has improved during the past decade, and whether the introduction of double-blind peer review (where reviewers are blinded to author names and vice-versa) improved female authorship rates. Methods: We analyzed authorship lists during a 10-year period (2007)(2008)(2009)(2010)(2011)(2012)(2013)(2014)(2015)(2016) from the 2 highest impact-factor RO journals: The International Journal of Radiat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 27 publications
2
4
0
Order By: Relevance
“…The findings of this study suggest that the gender inequity in academic publications in JMIRO is similar to those reported in other radiology and radiation oncology journals as listed in Table 1. [6][7][8][9][10] Similar findings were also reported in other oncology specialties including surgical oncology and clinical oncology in 2017 where the representation of women as first and senior authors was 37% and 29% respectively. 12 The results of this study showed that the proportion of women as first author was 30% and 41% MI and RO articles respectively.…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…The findings of this study suggest that the gender inequity in academic publications in JMIRO is similar to those reported in other radiology and radiation oncology journals as listed in Table 1. [6][7][8][9][10] Similar findings were also reported in other oncology specialties including surgical oncology and clinical oncology in 2017 where the representation of women as first and senior authors was 37% and 29% respectively. 12 The results of this study showed that the proportion of women as first author was 30% and 41% MI and RO articles respectively.…”
Section: Discussionsupporting
confidence: 78%
“…5 Depending on the discipline, the rate of increase in women authors is estimated to be 0-1% per year. 5 While there is literature addressing gender differences in authorship in major radiology and radiation oncology journals, [6][7][8][9][10] there has been no previous assessment of potential gender differences in the authorship of scientific publications in the Journal of Medical Imaging and Radiation Oncology (JMIRO). JMIRO is the official journal of The Royal Australian and New Zealand College of Radiologists (RANZCR), publishing articles of scientific excellence in both medical imaging and radiation oncology.…”
Section: Introductionmentioning
confidence: 99%
“…Zayed et al previously reported that, in the 10-year period of International Journal of Radiation Oncology, Biology, Physics and Radiotherapy & Oncology journal publications between 2007 and 2016, there was an overall increase in the mean percentage of female authors in radiation oncology from 24% to 35%, but there was no significant increase in the proportion of first or senior authors. 14 Additionally, Ahmed et al reported that for the International Journal of Radiation Oncology, Biology, Physics publications between 1980 and 2012, there was a significant increase in the percentages of both female first authors (13.4%-29.7%) and female senior authors (3.2%-22.6%). 15 Holliday et al reported that from 1996 to 2012, women in radiation oncology had a lower median number of publications in comparison to male counterparts in regard to academic position, except assistant professors.…”
Section: Discussionmentioning
confidence: 99%
“…After adoption of this process there was an increase in mean percentage of female authors on articles at the Red Journal (27.4% [2007-2011] vs 34.0% [2012][2013][2014][2015][2016]; P = .012). 18 It was also found that the majority of authors and reviewers favored the double-anonymized review process, with only 6% of authors and 13% of reviewers disagreeing that double-anonymized review should continue at the Red Journal. 19 Indeed, this has allowed our small subspecialty journal to act as a model for other medical journals more generally.…”
Section: Int J Radiationmentioning
confidence: 99%